EVALUASI KERAPATAN JARINGAN STASIUN HUJAN TERHADAP KETELITIAN PERKIRAAN HUJAN RANCANGAN PADA SWS NOELMINA DI PULAU TIMOR - Krisnayanti, Denik Sri (Jurnal Teknik Sipil, 2011)
ABSTRACTRaining is the main component of hydrology process. The quality and quantity ofthe raining data determine the degree of precision on the planning and preservation ofwater resources. To get the accurate data, there are many things will be focused such asthe condition of raining station data, density and scattered station and the accuraterecording itself. In this research, the pattern of the net of raining recording station thatwill be used is the Kagan Net Method and the triangles of Kagan will be drawned byusing AutoCAD 2007.Timor island has two catchment area according to the river such as Benanain’scatchment area and Noelmina’s catchment area which have so many raining recordingstations scattering around it. This research will focus on Noelmina river flow area(2.036,544 km2) which has six raining recording stations.Based on analytical results, the coefficient of correlation on daily raining is0,389 and monthly raining is 0,555. These values are the mean values of all rainingrecording station on Noelmina river flow area. Based on WMO (World MeteorologicalOrganisation) for tropical zone such as Indonesia, the density of the nets should be 250-1000 km2/station, so that the density of the nets now has enough the standard that is339,424 km2/station, but the amount of existing station is less than the amount of stationrequired by Kagan method and it’s necessary to get more raining stations. For eacherror of minimum values 5% and 10% for daily raining are needed 39 stations with thedensity 52,219 km2/station and 11 stations with the density 185,140 km2/station.Meanwhile for each error minimum values 5% and 10% for monthly raining are needed37 stations with the density 55,042 km2/station and 10 stations with the density 203,654km2/station. The amount of stations is not the only one factor that effecting the precisionof raining forecasting, but also there would be the pattern of scattering of rainingrecording stations.ABSTRAKSIKomponen masukan utama dalam proses hidrologi adalah hujan. Kualitas dankuantitas data hujan menentukan kualitas ketepatan perencanaan dan pengelolaansumber daya air sehingga untuk memperoleh data yang akurat perlu diperhatikankondisi stasiun hujan, jumlah stasiun hujan, kerapatan dan pola penyebaran sertaketelitian pencatatannya. Pada penelitian ini metode pola jaringan yang digunakan yaitumetode jaringan Kagan dan penggambaran simpul-simpul segitiga Kagan menggunakanAutoCAD 2007.Pulau Timor memiliki dua wilayah sungai yakni Wilayah Sungai (WS) Benanaindan Wilayah Sungai (WS) Noelmina dengan jumlah pos stasiun hujan yang cukupbanyak dan menyebar. Penelitian dikhususkan pada DAS Noelmina yang mempunyaienam pos stasiun hujan dengan luas areal 2.036,544 km2.Berdasar dari hasil analisis, didapatkan koefisien korelasi untuk hujan harian 0,389 danhujan bulanan 0,555. Nilai koefisien korelasi ini adalah nilai rata-rata pada semuastasiun hujan pada DAS Noelmina. Berdasar pedoman yang dikeluarkan WMO (WorldMeteorological Organisation) untuk daerah tropik seperti Indonesia, dalam keadaanyang sulit dianjurkan kerapatan sebesar 250-1000 km2/stasiun sehingga kerapatanstasiun hujan untuk kondisi DAS Noelmina sekarang cukup memenuhi syarat yakni339,424 km2/stasiun, namun jumlah stasiun yang ada masih lebih kecil dibandingkandengan jumlah stasiun yang dituntut dengan cara Kagan sehingga diperlukanpenambahan jumlah stasiun. Untuk masing-masing kesalahan perataan minimum 5%dan 10% pada hujan harian, dibutuhkan 39 stasiun hujan dengan kerapatan 52,219km2/stasiun dan 11 stasiun hujan dengan kerapatan 185,140 km2/stasiun. Sedangkan,untuk masing-masing kesalahan perataan minimum 5% dan 10% pada hujan bulanandibutuhkan 37 buah stasiun hujan dengan kerapatan 55,042 km2/stasiun dan 10 buahstasiun hujan dengan kerapatan 203,654 km2/stasiun.